Evaluation of the emergency procedure in cases of dental avulsion among different professionals in the city of São José dos Campos-SP - Matias, Murilo; Fernandes, Ludimila Santos; Araujo, Marcelo Marotta (Brazilian Dental Science, 2014)
Objective: To assess the knowledge of the immediate action to be taken in cases of tooth extraction among professionals from different areas who witness this type of trauma in the city of São José dos Campos - SP, as well as guide them to the conduct immediately to be taken, since the prognosis of avulsed teeth element is directly related to the time it takes to replanted in respective alveolus. Besides the time factor, other factors such as management of the tooth, storage environment, treatment of the replanted tooth and preservation technique also have influence on the best prognosis.Material and Methods: For the development of the survey 50 professionals were randomly selected from the following professions: firefighters, doctors, nurses, teachers and dentists in different workplaces and from both genders. An evaluation was made through a questionnaire related to emergency treatment in cases of dental avulsion. The same was applied to all professionals, and questions were answered in the same period of time.Results: All data obtained was evaluated and a statistical analysis was performed. The professionals interviewed had low knowledge about the emergency procedure to be performed in cases of tooth avulsionConclusion: Even seen that part of the dentists are unaware of the appropriate techniques for this procedure, it was concluded that there is a great need for scientific and technical knowledge by this professional which would result in better patient care and more clarification on the subject the population.